Smoking status and racial/ethnic disparities in youth exposure to tobacco advertising. Issue 3 (4th August 2022) - Nicksic, Nicole E.; Bono, Rose S.; Rudy, Alyssa K.; Cobb, Caroline O.; Barnes, Andrew J.
Abstract: Tobacco advertising exposure increases tobacco use among youth. Data were from a largely racial and ethnic minority sample (60% non-Hispanic (NH) Black/African American) of youth (13–18 years) who were nonsmokers susceptible to future tobacco use ( n = 686) or current cigarette smokers ( n = 674). Regression models tested associations between tobacco advertisement exposure and smoking status, and determined demographic correlates. Nearly all youth recalled seeing a tobacco advertisement (98%), which was associated with smoking (OR = 1.12; 95% CI = 1.08–1.15). Racial minority youth had higher exposure to tobacco advertising. Policies restricting advertisements for all tobacco products are essential for prevention efforts and may help decrease tobacco-related health disparities.